Role Of Teaching Materials On English For Young Learners - Nuralisa Nuralisa; Rahmadi Nirwanto (BADAN PENERBIT STIEPARI PRESS, 2023)
Teaching and learning materials are one of the most crucial elements that must be available in order to carry out teaching and learning activities. Teachers create materials because they are always trying to match resources with what their pupils need. They accomplish this by selecting, revising, and adding materials as they organize their classes. They also assess their materials as they go along based on how their students are responding. In this study, the development of EYL teaching and learning tools is discussed. This study falls under the category of document research, commonly known as library research. When conducting research in a library, the information is acquired from a variety of sources, including